Public perspectives on COVID-19 triage protocols for access to critical care in extreme pandemic context. - Marie-Eve Bouthillier; Yanick Farmer; Claudia Calderon Ramirez; James Downar; Andrea Frolic; Joseph Dahine; Lucie Opatrny; Diane Poirier; Gina Bravo; Audrey L'Espérance; Antoine Payot; Peter Tanuseputro; et al. (PLoS ONE)
COVID-19 triage protocols are resource allocation processes to deal with the potential lack of resources in Intensive Care Units (ICU). They have given rise to numerous ethical issues and controversies. Among them is the fear that people will be denied access to ICU on the basis of judgments about their quality of life, social value, frailty or age. This online Democratic Deliberation (DD) with members of the public aimed to discover the necessary considerations and conditions that make triage protocols more acceptable to guide future decisions in terms of the values and criteria that must underpin triage protocols. We simultaneously conducted the online DD in Quebec and Ontario on May 28th and June 4th, 2022, among adults who do not work in the healthcare sector, recruited randomly among the members of the public registered on Leger Opinion poll website to favor sociodemographic diversity. Data was analyzed using thematic analysis. Among the participants who took part in the study, 27 participants were from Ontario and 20 from Quebec. Three main themes emerged: 1) Acceptance of the protocol and values, 2) Considerations to be integrated in triage protocols, 3) Conditions which may favor a greater public acceptance of these protocols. Participants supported the idea of prioritizing patients with the best prognosis of survival under extreme conditions. The maximization of benefits was the most predominant approach. Participants considered that triage protocols are necessary to reduce arbitrariness in decision making and to facilitate these tragic decisions by health professionals.